FORMULASI SEDIAAN FACE SPRAY EKSTRAK KULIT LEMON (Citrus Limon L.) SEBAGAI PELEMBAB WAJAH: Formulasi Sediaan Face Spray Ekstrak Kulit Lemon (Citrus Limon L.) Sebagai Pelembab Wajah - Ramadhan, fitra Isnaini Wulan; Saryanti, Dwi (Jurnal Ilmiah JOPHUS : Journal Of Pharmacy UMUS, 2024)
Lemon fruit skin contains flavonoid compounds which can moisturize human skin. The aim of this research was to determine the concentration of lemon peel extract (Citrus limon L..) as a facial moisturizer. The face spray preparation was then made into three formulations consisting of 5%, 7.5% and 10%, then physical properties were tested, pH test, clarity test, homogeneity test, specific gravity test, viscosity test, irritation test and moisture test. The results obtained from testing the physical properties of lemon peel extract face spray preparations, both formulas 1, 2 and 3, produced good physical quality and obtained moisture from the lemon peel extract face spray, namely in formula 1 it was 38.1%, formula 2 was 53. 1% and formula 3 58.9% which is included in the moist category, so it can be concluded that the face spray preparation of lemon peel extract with the best concentration, namely formula 3, can moisturize the face. The stability results of the face spray preparation were stable using the freeze thaw method